2011
DOI: 10.4314/ijbcs.v5i3.72279
|View full text |Cite
|
Sign up to set email alerts
|

Etude dynamique des apports en éléments majeurs et nutritifs des eaux de la lagune de Porto-Novo (Sud Bénin)

Abstract: Afin d'évaluer le niveau trophique de la lagune qui expliquerait la prolifération des algues sur la lagune, les nutriments (NTK et phosphore total) et la Demande Chimique en Oxygène (DCO) des eaux de la lagune Porto-Novo ont été déterminés suivant les quatre saisons de l'année. L'étude a également permis d'analyser par chromatographie les éléments minéraux, anions et cations, dans les eaux de la lagune. Les résultats ont montré que les concentrations en chlore (variant entre 0,84 et 1180 mg/L) et en sodium (va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 6 publications
0
6
1
3
Order By: Relevance
“…Maximum sulphates and magnesium levels in waters are recorded during long rainy season and short rainy season, respectively. This is not the case of Coatzacoalcas estuary in Mexico, lagoon of Porto-Novo and hydrosystem Lake Togo -Lagoon of Aného in Benin where Hoz et al (2003), Mama et al (2011) andOuro-Sama et al (2018), respectively, have reported high sulphates and magnesium levels in dry season or in période of oceanic influence. These high sulphates and magnesium levels during rainy seasons are due to anthropogenic factors (Assemian-Niango et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Maximum sulphates and magnesium levels in waters are recorded during long rainy season and short rainy season, respectively. This is not the case of Coatzacoalcas estuary in Mexico, lagoon of Porto-Novo and hydrosystem Lake Togo -Lagoon of Aného in Benin where Hoz et al (2003), Mama et al (2011) andOuro-Sama et al (2018), respectively, have reported high sulphates and magnesium levels in dry season or in période of oceanic influence. These high sulphates and magnesium levels during rainy seasons are due to anthropogenic factors (Assemian-Niango et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…INTRODUCTION L'étude de la qualité physicochimique et l'évaluation du niveau trophique des cours d'eau permet de caractériser ces éléments minéraux qui dégradent la qualité des cours d'eau et menacent la vie aquatique (Mama et al, 2011a). L'eutrophisation est un phénomène caractérisé par un déséquilibre écologique avec, au départ, une fertilisation excessive en éléments minéraux et organiques d'origine anthropique.…”
Section: Resumeunclassified
“…In addition to anthropogenic sources of nitrogen, the use of phosphorus in detergents and other chemicals increases the phosphate load in raw water. The metallurgical industry and the erosion of rocks can justify the presence of metals in these waters (Mama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%